Comparative study to determine the prevalence and socio-cultural practices of infertility in Rural and Urban field practice area of Tertiary Care Hospital, Vijayapura, Karnataka - Rekha Udgiri; Vidya V Patil (Wolters Kluwer Medknow Publications, 2019)
Background: Infertility is an iceberg phenomenon where the majority of couples are undiagnosed. The main challenge in estimating the actual burden of infertility is the paucity of population-based studies. Various sociocultural practices such as believing infertility as curse and seeking healing from supernatural powers are still predominant in the community. Hence, the present study was undertaken to know the prevalence and sociocultural practices of infertility in field practice area. Materials and Methods: A cross-sectional study was conducted in rural and urban field practice areas of tertiary care hospital. A complete enumeration of all the houses was done to list all the eligible couples residing in the area; among them, those at risk of pregnancy were identified so as to find out couples with either primary or secondary infertility. Data were tabulated and analyzed using the SPSS software version 16. The results were expressed in terms of percentages, and Fisher's exact test was used wherever applicable. Results: The prevalence of infertility in rural area was 7.6% and in urban slum, it was 8.8%. Most of them think infertility as a result of past sins and practice unscientific methods to overcome the problem. Conclusion: Infertility stigma is high and there is no proper knowledge about infertility, fertile period and most of them think it as result of past sins.